Penyebab Siswa Putus Sekolah (Studi Kasus Anak SMP di Kelurahan Bungus Teluk Kabung Utara Kecamatan Bungus Teluk Kabung Kota Padang) - wati, Sorga - (Pendidikan Sosiologi, 2014)
This research is background because the purpose of this research is about the reason why student stop studying because of the social phenomena that happening in society because education is the most important and main thing meanwhile based on social phenomena the low of self interesting in continuing Junior High School. The theory which is used in this research is strukturasi Giddens. The approoachment which is used in this research is qualitative method by descriptive type or research to give description about reality which is being observed. The informant in this research is 34 people purposive sampling technique in this student who stop studying is 26 people and 15 parents and also 2 teachers who teach in Kelurahan Bungus Teluk Kabung Utara. The data collection is done by observation and dept interview and documentation. Data analysis unit are individual, and data analysis which is used by data collecting , data reduction, and data served (data analysis) , and verification and taking conclusion. Based on research result which is done, the reason why student stop studying is because the environment of those students which make student canât go to school anymore, because the economic condition of their parent canât make them schooling because thereâs lack of importance of education from their parents